An overview of different distillation methods for small scale applications - Saidur, Rahman; Elcevvadi, E.T.; Mekhilef, Saad; Safari, Azadeh; Mohammed, Hussein A. (Elsevier, 2011)
Many countries now suffer from shortage in fresh water, hence, currently 125 countries around the world are taking advantage of desalination methods to access fresh water from brackish and seawater. As desalination is one of the important processes for producing potable water that can be used for human consumption, irrigation and industry. In the last decades, many researchers have been conducted to minimize the cost of this process, and several methods have been developed. Among these methods, distillation appears as one of the best practical and the most economical, especially for mass production of fresh water from high saline water like seawater. On the other hand, most of the ongoing desalination researches concentrate on large-scale plants which are suitable for mass production of fresh water. A few researches have been conducted on small scale water distillation. This study will focus on different distillation methods for small scale production of potable water which is suitable for domestic, small factories, laboratories, and emergency use. This review presents various technologies available for small scale distillation with focus on Refro-distiller systems. Consequently, the theoretical analysis to determine the efficiency and energy costs are presented.